The second person reference in the Rio Branco dialect - Camacho, Roberto Gomes [UNESP]; da Silva, Marinete Rodrigues (Universidade Estadual de Maringa, 2021)
A variable that runs through almost all Brazilian Portuguese dialects is the alternation between the pronouns ‘tu’ and ‘você’ to refer to the interlocutor, a phenomenon that has been addressed in by researchers from different theoretical perspectives, including Menon (2000), Corrêa (2002), Lorengian-Penkal (2004), Lucca (2005), Dias (2007), Lopes (2007) and Franceschini (2011). This paper aims at focusing on this alternation in the in the variety of Portuguese spoken in Rio Branco, Acre, with the specific purpose of examining whether this phenomenon is a case of true variation in which the selection of one of the variants may represent a mark of social identity by virtue of a possible assigning of prestige or stigma or whether, alternatively, it is a case of a truly functional choice in which both forms alternate to yield different discursive effects in terms of determining the reference to the second person. The investigation of ‘tu’ and ‘você’ departs from the database collected by the project Estudo da Fala Urbana de Rio Branco, which is composed of narratives of personal experience. This corpus was elicited and transcribed by researchers of the Grupo de Pesquisa Ecossistema Linguístico do Acre. The results point to an expressive predominance of ‘você’ in undetermined reference. When determined reference is at issue, the use of ‘você’ is preferred by informants with higher education level, and the use of ‘tu’ is preferred by informants with elementary and high school education level. This distribution clearly shows the assigning of a prestige value to the use of ‘você’. Some cases of reported speech utterances were identified which represent a context potentially accessible to different role relationships between the interlocutors involved. In this context, choosing ‘tu’ or ‘você’ is motivated by the interaction situation: ‘você’ is used to indicate distance and formality and ‘tu’ is used to indicate familiarity and informality.
A referência à segunda pessoa na variedade rio-branquense
Keywords: 2nd person pronoun; Determined reference; Sociolinguistic variation; Undetermined reference